Optimalisasi Keuntungan Menggunakan Metode Simpleks Pada Produksi Batu Tela - Vinsentius Ngamelubun; Muhammad Zulkarnain Sirajuddin; Rovalino Lundi Lucky Salambauw; Jody Imanuhua; Fedinan Edmar Fossa; Leonardo Maha; Matheus Supriyanto Rumetna; Tirsa Ninia Lina (STMIK Budi Darma, 2019)
Tela stone is a building material that is needed, especially in various regions of Indonesia which are currently under construction, especially in Sorong City, West Papua Province. XYZ tela stone maker located in Jalan Srikandi Kilometer 12 Sorong City, is one of the business of tela stone makers who strive to survive and continue to develop production. To maintain the availability of production results need to take steps to maximize profits. The simplex method is the method used in this study as well as the POM-QM for Windows tool to estimate the maximum profit gained from each production made in one month quickly and accurately, so that it has an accurate calculation estimate. The result of calculation of maximum profit in one month is IDR 6,000,000